ANALISIS PENGAWASAN CAMAT DALAM PENGELOLAAN ALOKASI DANA DESA DI KECAMATAN TRIMURJO KABUPATEN LAMPUNG TENGAH - Ani Heryani; Ade Iskandar; Basromi Ali (Universitas Bandar Lampung (UBL), 2020)
The problems in this research are: (1) How to Supervise the Head of Sub-District in the Implementation of Village Fund Allocation in Trimurjo District, Central Lampung Regency. (2) What are the aspects that support and hinder the supervision of the Camat in the allocation of Village Funds in Trimurjo District.The research method used is qualitative with descriptive analysis method, the use of this method is to describe and study qualitatively, the supervision of the sub-district head in managing the Village Fund Allocation in Trimurjo District, Central Lampung Regency, qualitatively examining how all data was obtained directly from informants in the field using interviews and document studies.The results showed that the supervision of the sub-district head in managing the Village Fund Allocation in Trimurjo District, Central Lampung Regency, in general has shown that the supervision of the Head of the Sub-District in the Management of Village Fund Allocation in the Trimurjo District, Central Lampung Regency, has been carried out by direct supervision by the Camat, namely by direct involvement. see the activities that are being carried out by the villages in implementing the Village Fund Allocation (ADD), then indirect supervision is carried out by the leadership, namely by monitoring the implementation of the Village Fund Allocation through monthly reports on the development of these activities.Aspects that hinder the supervision of the Head of Sub-district Supervision in the Management of Village Fund Allocation in Trimurjo District, namely (1) The duties of the leadership are relatively many so that direct supervision in the implementation of Village Fund Allocation in Trimurjo District, in general the implementation of supervision has been running well. (2) Relatively low indirect supervision, so as to reduce the level of implementation of Village Fund Allocation in Trimurjo District. (3) Villages in Trimorjo Subdistrict, Central Lampung Regency, in implementing Village Fund Allocation, have not fully implemented activities properly without any supervision in carrying out their activities.